Analisis framing media massa dalam aksi demo pemuda pancasila - Umniatun Najihah (Universitas Garut, 2023)
Abstract Indonesia is a country that adheres to a democratic system, which means that every citizen has full power over their government. Demonstrations are one way for certain groups to voice their opinions, as was done by the Pancasila Youth Mass Organization on November 26 2021. However, the demonstration held by Pancasila Youth at the DPR Building ended in chaos and attracted the attention of online media to frame the demonstration in accordance with perceptions. each media. This research aims to identify news related to the Pancasila Youth Demonstration in Online Media (Jpnn.com, and Kompas.com) November 2022 edition. The theory used in this research is mass media construction. This research uses Robert N. Entman's framing method with a qualitative approach . The results of the research show that the formulation of the problem is that there was a demonstration attended by Pancasila Youth in front of the DPR building. The demonstration was held to protest against the statement by Deputy Chairman of Commission II of the DPR, Junimart Girsang, who asked that mass organizations that often cause trouble and get involved in clashes be disbanded. The diagnosis of the cause is that the source of the problem in this case is Pemuda Pancasila as the organizer of the demonstration which was held in front of the DPR Building, however, according to tribunnews.com and Jpnn.com, this is still under investigation. Make moral judgments by always maintaining your attitude and maintaining peace in society, you must respect each other so that peace can be achieved and become a good example for society. The treatment recommendation from the three media is to continue to follow the law and carry out the legal processes that have been determined. Keyword: Framing Analysis; Demonstration Action; Online media. Abstrak Indonesia merupakan negara yang menganut sistem demokrasi yang berarti setiap warganya memiliki kekuasaan penuh atas pemerintah mereka. Demonstrasi menjadi salah satu cara kelompok tertentu untuk menyuarakan pendapatnya seperti yang dilakukan oleh Ormas Pemuda Pancasila pada 26 November 2021. Namun, Aksi Demo yang diselanggarakan Pemuda Pancasila di Gedung DPR tersebut berujung Ricuh dan menarik perhatian para Media Online untuk mebingkai aksi demonstran tersebut sesuai dengan persepsi masing masing media. Penelitian ini bertujuan untuk mengidentifikasi Pemberitaan Terkait Aksi Demo Pemuda Pancasila pada Media Online ( Jpnn.com, dan Kompas.com) edisi November 2022. Teori yang digunakan dalam penelitian ini adalah konstruksi media massa Penelitian ini menggunakan metode analisis framing Robert N. Entman dengan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa define problem yakni terjadinya aksi demo yang diselenggarakan oleh Pemuda Pancasila di depan gedung DPR. Demonstrasi digelar untuk memprotes pernyataan Wakil Ketua Komisi II DPR Junimart Girsang, yang meminta ormas yang kerap berbuat onar dan terlibat bentrokan dibubarkan. Diagnose cause yaitu sumber masalah dari kasus ini adalah Pemuda Pancasila selaku penyelenggara aksi demo yang dilakukan di depan Gedung DPR, namun berdasarkan tribunnews.com dan Jpnn.com hal ini masih dalam taham penyelidikan. Make moral judgment dimana selalu menjaga sikap dan menjaga kedamaian di tengahtengah masyarakat, harus saling menghormati antar satu sama lain sehingga mewujudkan perdamaian dan menjadi contoh yang baik untuk public. Treatment recommendations dari tiga media adalah terus mengikuti jalur hokum dan menjalankan sekala proses hokum yang telah ditetapkan. Kata-kata Kunci: Analisis Framing; Aksi Demo; Media Onlie.